Responses of Arab teachers of Hebrew in Israel to an Israeli novel on Jewish-Arab relations. Issue 2 (9th January 2020) - Rudin, Shai
Abstract : Purpose: This study aims to examine the responses and perceptions of Israeli Arab teachers toward multicultural and educational issues concerning Jewish–Arab relations. Design/methodology/approach: This study is a qualitative research. The study included 44 novice Arab teachers, who teach Hebrew in the Arab sector and are currently studying toward their masters' degree at a teacher education college in northern Israel. The teachers were asked to read the novel Nadia by Galila Ron Feder–Amit. Published in 1985, the novel describes the complex integration of Nadia, an Arab village girl, into a Jewish boarding school, and it is narrated in first person. After having read the novel, the teachers were requested to answer the writing task, which addressed the character of the protagonist, the issue of teaching the novel in the Jewish and Arabic educational systems and the anticipated responses of Jewish and Arab students to the novel. Findings: Phenomenological analysis of the teachers' responses found that the reading experience was complex and resulted in a variety of responses toward the protagonist. Some were based on identification and appreciation, while others on criticism and judgment of the heroine's restraint vis-a-vis the racism that she was experiencing. However, most of the teachers demonstrated moral courage and thought that the novel should be taught, as they viewed it as a bridge leading to understanding between the two nations. The teachers anticipated conflicting responses of Jewish and Arab students to the novel, according to the students' political views and values. Practical implications: These findings indicate that the educational system should include political texts relating to the Jewish–Arab schism, especially texts that voice the Palestinian narrative. This view differs from the current situation in both sectors, whereby the tendency is to avoid political texts while ignoring the Palestinian narrative. Originality/value: The study shows that the reading experience of a political novel affords various and often contrasting responses with the teachers facing the didactic challenges. The teachers who participated in the study anticipated complexity of the reading and teaching process, yet were not deterred by it, particularly in view of the novel's messages – striving to understand the "other" and to bridge a discourse between the nations.